THE CLINICAL SIGNIFICANCE OF THE ULNAR NUTRIENT FORAMEN: A MORPHOLOGICAL ANALYSIS. - Mahesh Dhoot; Hemant Ashish Harode; Vivek Kumar (Student's Journal of Health Research, 2023)
Background: The arteries that provide nutrients to the bone enter the bone of the ulna through the nutrient foramina. During bone grafting, it is necessary to understand the position and number of nutrient foramina to ensure that the bone grafts have a good supply of vessels and that the blood vessels are not damaged. In this research, the morphology of nutrient foramina on the Human ulna bone is studied. Methods: 100 ulna bones were procured from the anatomy department of Shivpuri, Madhya Pradesh. The bones were taken for study irrespective of gender or age. The bones were examined to determine the side of the ulna. The bones were thoroughly observed for the position and number of nutrient foramina. The nutrient foramina was located and marked. The bone's length and distance of the foramina from the end of the bones were determined and put into Hughes's formula to calculate the foramina index. The data obtained was statistically analyzed. Result: The nutrient foramina was located towards the end of the bone. Out of all bones, only 6% had two nutrient foramina; the rest all had one nutrient foramina. The relation of bone length to the number of nutrient foramina was not significant. According to the foramina index calculated, most of the nutrient foramina were located on the anterior part of the third of the middle part of the bone; the mean foramina index was 36.48. Conclusion: From this study, the morphology of the nutrient foramina on the ulna bones can be understood. This helps the surgeons during bone grafting to protect the location of the foramina so that the ulna remains vascularized. Recommendation: We recommend a Computed Tomography (CT) scan of the fracture to assess fragment sizes, displacement, and suitability for primary fixation.